Bisphenol A – A problem for consumers of canned beer? Potential risks and analysis of debatable plastics used in canned beer coatings - Garbe, Leif-Alexander; Neumann, Konrad; Rettberg, Nils (BrewingScience, 2010)
The precise determination of Bisphenol A (BPA) amounts in complex matrix like beer is presented. A practical, rapid and reliable sample preparation procedure for BPA determination is shown. The application of stable isotope dilution assay (SIDA) utilizing labmade deuterated BPA standards made it possible to obtain accurate analytical data. BPA concentrations in seven randomly chosen canned beers ranged from 1 μg BPA/L to 6.5 μg BPA/L. Compared to other canned foodstuff these amounts are low and presumably safe.